Integrated Production and Distribution Planning using Mathematical Model for Maximizing Profit - Lely Herlina; Muhammad Adha Ilhami; Kiki Dwi Safitri (Jurnal Ilmiah Teknik Industri, 2022)
In three-dimensional concurrent engineering context, product, process, and supply chain designs are approached by the imperative of concurrency principle. The imperative of concurrency proposes product architecture and supply chain architecture conducted simultaneously. The detailed product design and production process design are conducted simultaneously. While manufacturing system design is conducted simultaneously with logistic system design. This study concerns on integrating production planning with distribution planning in a new plastic bags plant. Since the plant is relatively new, the number of orders is still scarce. Therefore, production planning becomes critical. Producing more products than required creates inventories while producing as many as the order required creates an intermittent production schedule. A mathematical is developed to simultaneously schedule production and distribution to maximize profit. The model provides solutions on the number of materials to be delivered, the number of products produced and delivered within its period for the planning horizon.